Social inequalities in injury occurrence and in disability retirement attributable to injuries: a 5 year follow-up study of a 2.1 million gainfully employed people - Tüchsen Finn; Nielsen Martin L; Mikkelsen Kim L; Hannerz Harald; Spangenberg Søren (BMC, 2007)
Abstract Background Inequalities in injury related disability retirement may be due to differences in injury risk and or differences in retirement given injury. The aim of the present study was to measure social inequalities in injury occurrence and injury related disability retirement. Methods All people in the Danish labour force aged 20-59 years 1 January 1997 were followed for injury related hospital contacts during 1997 and all people in the Danish labour force aged 21-54 years 1 January 1998 were followed for injury related hospital contacts during 1997 and for disability retirements during 1998-2002. As inequality indices we used excess fractions (EF) i.e. the proportions of the cases that would not have occurred if the risks in each social group had been as low as they were in the occupational group with the highest skill requirements. Results With regard to the risk that an injury will occur, the EF was 36% among men and 10% among women. With regard to the risk that an injury will lead to disability retirement, the EF was 43% among men and 47% among women. The combined effect of the two types of inequalities rendered an EF for injury related disability retirement of 64% among men and 53% among women. The correlation between the case disability rate ratios among men and those among women was low (r = -0.110, P = 0.795). Conclusion The social inequality in injury related disability retirement lies only to some degree in the differences in the injury risk. More important are differences in the consequences of an injury. This was especially pronounced among the women.